2020
DOI: 10.3389/fneur.2020.593074
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for the Prediction of Cessation of Migraine Among Patients With Patent Foramen Ovale After Percutaneous Closure

Abstract: Objective: This study aimed to develop and validate a nomogram to predict cessation of patent foramen ovale (PFO) patients with migraine headache after percutaneous closure. Methods: A total of 247 eligible patients with PFO and migraine after percutaneous closure between May, 2016 and May, 2018 were divided into a development cohort (n = 149) and a validation cohort (n = 98). The primary end point was cessation of migraine at follow-up of 1 year after the procedure measured by the Migraine Disability Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although the PREMIUM and PRIMA trials failed to conclude that PFO closure is effective for migraineurs with PFO ( Mattle et al, 2016 ; Tobis et al, 2017 ), we still cannot say it is completely useless. A recent study developed a nomogram that included migraine with aura, antiplatelet history, and right-to-left shunt at rest had good predictive accuracy for migraine cessation in patients with PFO after PFO closure ( Zhao et al, 2020 ), which means that PFO closure is an effective treatment for at least some PFO migraineurs. This study demonstrates that changes in brain activity during photic stimulation, such as occipital beta band PSD, have the potential to be at least a supplementary marker for predicting the effectiveness of PFO closure for migraineurs with PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Although the PREMIUM and PRIMA trials failed to conclude that PFO closure is effective for migraineurs with PFO ( Mattle et al, 2016 ; Tobis et al, 2017 ), we still cannot say it is completely useless. A recent study developed a nomogram that included migraine with aura, antiplatelet history, and right-to-left shunt at rest had good predictive accuracy for migraine cessation in patients with PFO after PFO closure ( Zhao et al, 2020 ), which means that PFO closure is an effective treatment for at least some PFO migraineurs. This study demonstrates that changes in brain activity during photic stimulation, such as occipital beta band PSD, have the potential to be at least a supplementary marker for predicting the effectiveness of PFO closure for migraineurs with PFO.…”
Section: Discussionmentioning
confidence: 99%
“…The association of migraine with patent foramen ovale, which is often complicated by ischemic brain damage, has been also found (Takagi and Umemoto 2015;Zhao et al 2020).…”
Section: Migraine and Ischemic Brain Damagementioning
confidence: 96%
“…Proposed mechanisms for this correlation include hypoxia, changes in cerebral autonomic regulation, and venous thromboembolism due to right-left shunting and in situ thrombosis within the PFO [6][7][8][9]. Furthermore, multiple studies have demonstrated that device closure of PFO may result in migraine relief [10][11][12][13]. However, none of the three randomized controlled trials (RCTs) on PFO closure achieved their primary endpoints, including migraine cessation, reduction in monthly migraine days, and responder rates [14][15][16].…”
Section: Introductionmentioning
confidence: 99%